Gifted children of color around the world diverse needs, exemplary practices and directions for the future. - Davis, Joy Lawson, 1953-; Moore, James L., III.; Lewis, Chance W. (Chance Wayne), 1972- (Bingley, U.K. : Emerald, 2016)
We live in a global society, wherein our dependence on our neighbors is growing more intensely each year. Technology, travel, and interdependent economic systems require that nations know more and share more of their natural resources. Among the most precious of these resources is the intellectual talent that resides in their countries. This edited volume sheds light on the unique challenges, trends, and intersecting issues related to identifying intellectual potential of children of color around the world, providing access to appropriate curriculum and instructional opportunities, addressing the professional capacities of teachers working with these students, and the role of diverse families and communities in the talent development process in these communities. To achieve the volume's objectives, the editors bring together expert scholars from around the world who have a vested interest in gifted children of color.
Gifted education programming: serving the native Peruvian / Sheyla Blumen -- Developing cultural competence in gifted and advanced students using community problem solving / Tarek Grantham, Margaret Hines, April Dennis, Marianne Solomon, Brittany Anderson -- Si se puede/yes we can: ramping up efforts for collaborating with Hispanic parents and families / Jaime Castellano -- Meeting the academic and socio-emotional needs of twice exceptional African American students through group counseling / Renae Mayes, Paul Harris, Erik Hines -- Talent in every community: a glimpse into the world of parenting gifted children of color / Joy Davis -- Where are all the Latino males in gifted programs? / Desiree Vega, James Moore III -- Teaching to their strengths: good medicine for Native American education / Jerry Lassos, Steven Haas -- Biracial and multiracial gifted students: looking for a grain of rice in a box of sand / Donna Ford, Gilman Whiting, Ramon Goings -- Brief overview of the current state of gifted education in the Dominican Republic / Leticia Jaquez, Roman Jaquez, D. Socorro Collado -- Gifted children of color in the Deep South / Kevin Besnoy, Camille Floyd, Elvira Deyamport, Ashley Cavan.
Includes bibliographical references.
Print version record
Keywords: Education -- Multicultural Education; Education; Gifted children -- Education; Children of minorities -- Education